Spatial Analysis of Benthic and Geomorphic Habitat Distribution in the Shallow Waters of Pombo Island, Indonesia, using High Resolution PlanetScope Satellite Imagery - Rifai , Ahmat; Halim; Rahayaan , Muhamad F. M.; Rakuasa, Heinrich; Rajani , La Mbeli (CV. Science Tech Group, 2025)
The benthic biodiversity-rich but degradation-prone coastal waters of Pombo Island, Maluku, were mapped using high-resolution PlanetScope (3m) satellite imagery and field data through a random forest approach. The results showed the dominance of inner reef flat (54%) and sand substrate (39.62%), with 22.31% coral cover, while geomorphological analysis revealed a strong correlation between sheltered reef slope (18.78%) and benthic habitat distribution (85% classification accuracy). These findings not only prove the effectiveness of remote sensing technology for tropical ecosystem monitoring but also recommend zoning-based conservation strategies, particularly reef crest protection and seagrass rehabilitation, as a contribution to sustainable environmental management in line with SDG targets.